Immunoadsorption in patients with neuromyelitis optica spectrum disorder. (July 2016) - Faissner, Simon; Nikolayczik, Johanna; Chan, Andrew; Gold, Ralf; Yoon, Min-Suk; Haghikia, Aiden
Introduction: Neuromyelitis optica spectrum disorder (NMOSD) is a neuroinflammatory disorder of the central nervous system, distinct from multiple sclerosis by affecting predominantly the optic nerve and the spinal cord, and mediated by antibodies directed against aquaporin 4 (AQP4-ab) as a possible pathomechanistic hallmark of NMOSD. Therapeutic options include immunosuppression with steroids or B-cell-depleting agents as baseline therapies, as well as plasma exchange (PLEX) and/or immunoadsorption (IA) during relapses. Until now, data concerning the efficacy of IA alone are scarce. Methods: Visual evoked potentials (VEPs), visual acuity and changes of symptoms at relapse leading to admission in NMOSD patients ( n = 10) treated with IA in a single-centre setting were evaluated retrospectively. Results: All patients profited from the procedure and showed an amelioration of admission symptoms. Three patients improved in visual acuity, another three patients remained stable, whereas five patients showed an improvement in VEPs. Discussion: In this small cohort, IA constitutes a valid therapeutic option for patients with NMOSD as an equivalent to PLEX. Analysis in larger cohorts is warranted.